2002
DOI: 10.1211/002235702760089081
|View full text |Cite
|
Sign up to set email alerts
|

Ruscogenin glycoside (Lm-3) isolated fromLiriope muscariinhibits lymphocyte adhesion to extracellular matrix

Abstract: We examined the effects of ruscogenin glycoside (Lm-3), isolated from Liriope muscari, on lymphocyte adhesion to extracellular matrix. Adhesion of Jurkat cells activated by anti-CD3 to type I collagen was inhibited by Lm-3 in a concentration- and time-dependent manner. Lm-3 also inhibited the cell attachment to fibronectin and laminin. However, the saponin did not influence anti-CD3-induced cell proliferation and Mn2+-induced adhesion. Protein kinase C activator, phorbol 12,13-dibutyrate, significantly enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…In addition, ruscogenin is also a major steroidal sapogenin of Radix Ophiopogon japonicus, a Chinese herb that has been used to treat acute and chronic inflammatory and cardiovascular diseases for thousands of years (4). The related pharmacological studies have been confirmed activities of the ethanol extract from Ophiopogon japonicus or ruscogenin glycoside in various aspects such as antiarrhythmia (5), anti-ischaemia (6), anti-thrombosis (7,8) effects; improving liver injury (9); and inhibiting inflammation (10,11). Our previous studies also showed that ruscogenin significantly inhibited the adhesion of leukocytes to ECV304 cells activated by tumor necrosis factor-α (TNF-α), while it had no remarkable effect on leukocyte adherence to resting ECV304 cells and cell viability, and also inhibited leukocyte migration in vivo.…”
mentioning
confidence: 94%
“…In addition, ruscogenin is also a major steroidal sapogenin of Radix Ophiopogon japonicus, a Chinese herb that has been used to treat acute and chronic inflammatory and cardiovascular diseases for thousands of years (4). The related pharmacological studies have been confirmed activities of the ethanol extract from Ophiopogon japonicus or ruscogenin glycoside in various aspects such as antiarrhythmia (5), anti-ischaemia (6), anti-thrombosis (7,8) effects; improving liver injury (9); and inhibiting inflammation (10,11). Our previous studies also showed that ruscogenin significantly inhibited the adhesion of leukocytes to ECV304 cells activated by tumor necrosis factor-α (TNF-α), while it had no remarkable effect on leukocyte adherence to resting ECV304 cells and cell viability, and also inhibited leukocyte migration in vivo.…”
mentioning
confidence: 94%
“…Extracts from this plant have been used in traditional medicine (Guarrera, 2005). Studies have shown that R. aculeatus extracts are active against blood disorders such as venous insufficiencies, edema, orthostatic hypotension, and inflammation (Liu et al, 2002;Huang et al, 2008;Mimaki et al, 1998). Notably, two saponin compounds found in the alcoholic extract of R. aculeatus inhibit the growth of the human promyelocytic leukemia cell line HL-60 (Lindequist, Niedermeyer & Julich, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Mice were sensitized by painting 0.1 mL of 1% picryl chloride in ethanol on the shaved skin of their abdomens. Five days later, they were challenged by painting 30 ·L of 1% picryl chloride in olive oil on the right ear lobe (Liu et al 2002). Eighteen hours later, the thickness of the right ear was measured against the left with a digimatic micrometer (0.001 mm; Mitutoyo Co., Tokyo, Japan).…”
Section: Picryl-chloride-induced Ear Contact Sensitivitymentioning
confidence: 99%